2009
DOI: 10.2478/v10042-008-0063-y
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of the bone marrow, spleen and liver during hematopoietic cell mobilization with cyclophosphamide in mice.

Abstract: Cyclophosphamide (CY), the agent with cytoreductive activity, is widely exploited in cancer chemotherapy, and can be used alone or in combination with various cytokines and growth factors to stimulate the egress of hematopoietic stem/progenitor cells (HSPC) from the BM compartment. The aim of the present study was to exam the morphology and ultrastructure of the bone marrow, spleen and liver of mice injected intraperitoneally with a single dose of cyclophosphamide (200 mg/kg bw) and the localization of cells e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Of note, we have found that CTX-induced DC expansion was preceded by proliferation of cells with DC phenotype (CD11c + CD11b + Ly6G − ) in the BM early (2–3 days) after CTX treatment [43]. This observation is consistent with the capability of CTX to induce mobilization of hematopoietic stem cells from BM to circulation alone or in combination with granulocyte-colony stimulating factor (G-CSF) [42; 44; 45; 46; 47; 48; 49]. These hematopoietic stem cells harvested from peripheral blood of cancer patients treated with CTX gave rise to higher yield of DCs in vitro than their control counterpart [50; 51; 52; 53; 54].…”
Section: Introductionmentioning
confidence: 64%
“…Of note, we have found that CTX-induced DC expansion was preceded by proliferation of cells with DC phenotype (CD11c + CD11b + Ly6G − ) in the BM early (2–3 days) after CTX treatment [43]. This observation is consistent with the capability of CTX to induce mobilization of hematopoietic stem cells from BM to circulation alone or in combination with granulocyte-colony stimulating factor (G-CSF) [42; 44; 45; 46; 47; 48; 49]. These hematopoietic stem cells harvested from peripheral blood of cancer patients treated with CTX gave rise to higher yield of DCs in vitro than their control counterpart [50; 51; 52; 53; 54].…”
Section: Introductionmentioning
confidence: 64%
“…This outcome supports findings by Barcew et al who demonstrated morphological destructive changes in the bone marrow and spleen of CP-treated mice. 64 Specifically, they observed significant decreases in cells on day 2 after intraperitoneal injection of 200 mg/g bw. A significant impact of CP on bone marrow, the primary site for hematopoiesis, could explain the time-related decreases in granulocyte levels in the other two sites as a result of the administration of 200 mg/g bw of CP.…”
Section: Discussionmentioning
confidence: 96%